Synthesis and investigation of singlet oxygen production efficiency of photosensitizers based on meso-phenyl-2, 5-thienylene linked porphyrin oligomers and polymers. Issue 42 (2nd September 2015) - Khan, Rehan; Idris, Muazzam; Tuncel, Dönüs
Abstract : Three new Zn(ii )-, oligo- and poly(2, 5-thienylene)-linked porphyrins, bearing multiple triethylene glycol (TEG) groups were synthesized and their photophysical properties as well as singlet oxygen generation efficiencies have been investigated to elucidate the possibility of their use as a photosensitizer. Abstract : Three new Zn(ii )-, oligo- and poly(2, 5-thienylene)-linked porphyrins, bearing multiple triethylene glycol (TEG) groups, on all meso aryl positions were synthesized via Stille and Suzuki coupling reactions and their photophysical properties as well as singlet oxygen generation efficiencies have been investigated to elucidate the possibility of their use as a photosensitizer for photodynamic therapy (PDT) and photodynamic inactivation of bacteria.